Euro Area Policies : Financial Sector Assessment Program-Technical Note-Bank Resolution and Crisis Management. (IMF Staff Country Reports; Country Report ;, 2018)
The euro area (EA) bank resolution and crisis management arrangements have been strengthened considerably over recent years, but work remains to complete and unify the regime. The adoption of the Bank Recovery and Resolution Directive (BRRD) and the Single Resolution Mechanism Regulation (SRMR), and the establishment of the Single Supervisory Mechanism (SSM) and the Single Resolution Mechanism (SRM) provide a foundation to deal with problem banks. The authorities remain committed to completing the banking union through the establishment of a backstop for the Single Resolution Fund (SRF) and a European deposit insurance scheme (EDIS) and other measures, many of which are in line with recommendations in this report.